Riesgo cardiovascular según las Tablas de Framingham por categorías en pacientes con SIDA, atendidos en consulta externa del Hospital Teófilo Dávila, de septiembre a diciembre del año 2011 - Betancourt Ushiña, Jorge L. (2012)
Using a cross-sectional, descriptive observational studied group of 150 patients with AIDS with and without antiretroviral therapy attending the outpatient hospital Teófilo Dávila Machala city in 2011, were used by the Framingham categories, the overall objective of the study was to determine the cardiovascular risk, and specific objectives determining cardiovascular risk according to age group, gender, and those with and without antiretroviral therapy.